Higher-order assemblies in immune signaling: supramolecular complexes and phase separation. Issue 9 (9th April 2021) - Xia, Shiyu; Chen, Zhenhang; Shen, Chen; Fu, Tian-Min
Abstract: Signaling pathways in innate and adaptive immunity play vital roles in pathogen recognition and the functions of immune cells. Higher-order assemblies have recently emerged as a central principle that governs immune signaling and, by extension, cellular communication in general. There are mainly two types of higher-order assemblies: 1) ordered, solid-like large supramolecular complexes formed by stable and rigid protein-protein interactions, and 2) liquid-like phase-separated condensates formed by weaker and more dynamic intermolecular interactions. This review covers key examples of both types of higher-order assemblies in major immune pathways. By placing emphasis on the molecular structures of the examples provided, we discuss how their structural organization enables elegant mechanisms of signaling regulation.